Firefighter asking questions about prototype firefighter uniform - Eisele, John, photographer (Colorado State University. Libraries, 2016)
Hallie Potthoff (left) Lauren White (center) Alan Fletcher (right).
The 2016 Fairmount Fire Rescue Fire Department Uniform Design was held at the Gifford Building, Colorado State University.
AM375.
SP2016 AM375 Firefighter Uniform Redesign.
Keywords: Fire departments -- Uniforms -- Design -- Awards; Fashion design -- Awards